Business plan: A preliminary approach to an unknown genre - Federico Navarro (Ibérica, 2022)
The business plan has been widely included in the curricula of economics degrees and is key to business practice worldwide, but has not been studied from a socio-discursive perspective yet due to restrictions in its social, spatial, and temporal circulation. Based on interviews and a qualitative analysis of a corpus of 38 texts written in Spanish, I aim to provide a preliminary description of the genre. Results indicate that a chain of four phases is associated to a continuum of social settings organized through entrepreneurial/corporate and expert/training variables; its rhetorical structure includes “describing present/potential situation of the company and market” and “describing future processes of strategic actions regarding the marketing, production, and financial plans”. This analysis offers methodological innovations to account for occluded genres, encourages the contrastive study of the business plan in different cultural and linguistic environments, and assists business teachers with a situated picture of the genre.